PENGARUH ARUS KAS OPERASI, STUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Kusumaningtyas, Ariyanti; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to obtain empirical evidences which are related to the influence of cash flow from the operation activity, ownership structure, and firm size to the financial performance in automotive companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. In this research the financial performance is proxy by the Return on Equity (ROE). The samples have been selected by using purposive sampling. The data employs the documentary data and the source data has been obtained from www.idx.co.id and the Investment Gallery of Indonesia Stock Exchange of âSTIESIAâ Surabaya. The data analysis technique of this research has been done by using classic assumption test and multiple linear regressions. The test which has been done by using Goodness of Fit states that the Operation Cash Flow, Ownership Structure, and Firm Size is the variable which is feasible to be used to explain the Return on Equity (ROE) variable. In addition, the t test shows that Cash Flow from the Operation Activity, Firm Size, and meanwhile Ownership Structure does not have any influence to the Return on Equity.Keywords: Cash Flow from the Operation Activity, Managerial Ownership Structure, Institutional Ownership Structure, Firm Size, Return on Equity.